2013
DOI: 10.1093/bioinformatics/btt093
|View full text |Cite
|
Sign up to set email alerts
|

Making automated multiple alignments of very large numbers of protein sequences

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…In all cases, the quality scores for the default guide trees fall off as the number of sequences increases, as was found in ref. 20. For chained trees, however, the quality scores fall off much more slowly than for either default or balanced trees.…”
Section: Resultsmentioning
confidence: 96%
“…In all cases, the quality scores for the default guide trees fall off as the number of sequences increases, as was found in ref. 20. For chained trees, however, the quality scores fall off much more slowly than for either default or balanced trees.…”
Section: Resultsmentioning
confidence: 96%
“…Performance studies have shown that some MSA methods can produce highly accurate alignments for large slowly evolving datasets (e.g., Sievers et al, (2013). However, studies focusing on phylogeny estimation with up to 28,000 sequences have shown that only SATé-I (Liu et al, 2009) and SATé-II (Liu et al, 2011) produced sufficiently accurate analyses of sequence datasets that are large and evolve under high rates of evolution.…”
Section: Introductionmentioning
confidence: 99%
“…We adapted the SeqTrack algorithm (17) to perform graph construction. Sequences were aligned using Clustal Omega 1.2.1 (34), and the resultant distance matrix was converted into a similarity matrix by taking 1 − distance. Affinity propagation (35) clustering was performed on each segment's similarity matrix to determine a threshold cutoff similarity value, defined as the minimum (across all clusters for that segment) of minimum in-cluster pairwise identities, below which we deemed it implausible for an evolutionary descent (clonal or reassortment) to have occurred (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic reconstruction was done for a subset of H3N8 viruses isolated from Minto Flats, Alaska, between 2009 and 2010 as part of a separate study. Briefly, each segment of the viral genomes was individually aligned, using Clustal Omega (34), and their genealogies were reconstructed, using BEAST 1.8.0 (36). A minimum of three Markov chain Monte Carlo runs that converged on a single optimal tree were chosen to compute the maximum clade credibility tree.…”
Section: Methodsmentioning
confidence: 99%